2021 Florida Plant Disease Management Guide: Eggplant - Shouan Zhang; Geoffrey Meru; Ken Pernezny; Aaron Palmateer (EDIS, 2022)
Summarizes specific common diseases affecting eggplant production in Florida, with symptoms and cultural controls. This version updated with new information by Geoffrey Meru.